Communication Apprehension among Students of Bangladesh: A Comparative Study between Online and Offline Classes - Razib, Mehedy Hassan; Pinky, Farzana Tasnim; Al-Zobayer, MD. (South Asian Journal of Social Sciences and Humanities, 2022)
This research study looks at students’ communication apprehension (CA) in online and offline  classes. We wanted to comprehend whether their concern has changed about CA during online  classes or not. In this quantitative research, we completed two surveys that asked them  demographic questions. Four hundred and ninety-nine (499) students of public universities took  part in online classes in August 2021 by completing the Personal Report of Communication  Apprehension (PRCA-24). Another survey was conducted on 438 students during the offline  classes in February 2022. We then analyzed the data in SPSS. The PRCA-24 scores of students  in both studies determine that most of the students have high communication apprehension. They  suffer from general anxiety, do not want to involve in any discussion during class, and have less  self-esteem. It has been found that students' fears of communication in academic settings  negatively affect their learning and performance. This study can be useful in communication  disorder discipline to find out where is the actual problem to communicate. This study will pave  the way for further research on what steps can be taken to overcome the problem of fear in  communication or whether any changes in teaching methods can be made.
Keywords: Communication apprehension; Online Education; PRCA-24; Fear of communication; Lower Self-esteem; Stage Fright